2009
DOI: 10.1021/ic801905p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Magnetism of Heterobimetallic Trinuclear Complexes {[L2Co2Ln][X]} [Ln = Eu, X = Cl; Ln = Tb, Dy, Ho, X = NO3; LH3 = (S)P[N(Me)N═CH−C6H3-2-OH-3-OMe]3]: A 3d−4f Family of Single-Molecule Magnets

Abstract: Sequential reaction of LH3 (LH3 = (S)P[N(Me)N=CH-C6H3-2-OH-3-OMe]3) with Co(OAc)2 x 4 H2O followed by reaction with lanthanide salts afforded trinuclear heterobimetalllic compounds {[L2Co2Ln][X]} [Ln = Eu (1), X = Cl; Ln = Tb (2), Dy (3), Ho (4), X = NO3] in excellent yields. These compounds retain their integrity in solution as determined by electrospray ionization mass spectrometry studies. The molecular structures of 1-4 were confirmed by a single-crystal X-ray structural study and reveal that these are iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(74 citation statements)
references
References 86 publications
6
68
0
Order By: Relevance
“…À11 s for known SMMs/SIMs; [4][5][6][7][8][9][10] the U eff value is comparable to that of the star molecule Mn 12 [1] and is remarkably larger than that of the […”
Section: -10mentioning
confidence: 99%
See 3 more Smart Citations
“…À11 s for known SMMs/SIMs; [4][5][6][7][8][9][10] the U eff value is comparable to that of the star molecule Mn 12 [1] and is remarkably larger than that of the […”
Section: -10mentioning
confidence: 99%
“…The ac oscillating frequencies corresponding to the observed peak temperatures were also fitted to the Arrhenius law, which gave a U eff value of 32.3A C H T U N G T R E N N U N G (2.6) K and a t 0 value of 2.5A C H T U N G T R E N N U N G (1.1) 10 À10 s (Figure 7). The t 0 value is also in the normal range for SMMs/SIMs, [4][5][6][7][8][9][10] but it is remarkably smaller than that of 1 (5.6 10 À6 s), and the U eff value of 2 (32.3 K) is clearly smaller than that of 1 (74.1 K). Further research into the dynamic magnetic behavior of 2 in the form of c'' versus c' plots are shown in Figure 8.…”
Section: -10mentioning
confidence: 99%
See 2 more Smart Citations
“…The Tb(III) and Ho(III) ions in transition metal clusters have been studied earlier in the context of the search for molecules that show SMM behavior [11][12][13]. Those studies have in common that they were performed using bulk techniques, such as magnetization and ac susceptibility measurements.…”
Section: Introductionmentioning
confidence: 99%